DYNAMICAL ANALYSIS OF CONTINENTAL OVERFLOW - Bailey R.C. (My University, 2001)
Recent field and laboratory studies indicate that the viscosity of the middle and lower continental crust may be 1018 Pa s or less in regions of high heat flow. Such strikingly low viscosities must strongly facilitate gravitational collapse of overthickened crust (thicker than would be possible without lateral tectonic support). In such areas, the ductile zone is so weak that lateral flow in it can relax all lateral pressure gradients in a geologically short time. The ductile or ''fluid'' zone is, for geological purposes, a fluid in hydrostatic equilibrium, floating a brittle cap of upper crust above it. A continent built in this way can collapse by overflow onto adjacent ocean basins if the continental elevation exceeds a critical threshold related to the mean geothermal gradient. This model permits relatively simple identification of the terms of the energy budget of gravitational collapse. Here I show that the budget is likely to be dominated by the balance between liberated gravitational energy (a source) and normal fault friction (a sink). Examination of this budget provides a stability criterion for gravitational collapse by continental overflow onto ocean basins: that crustal elevation above the ocean basin beyond an amount between a third and a half of the brittle cap thickness should drive a propagating overflow front.